The Role of Gamification Elements in Digital Banking among Gen Z Customers: A Gender-Based Analysis - Tetty Rimenda; Rahmanita Vidyasari; Kanako Alissya Sowiyk; Liska Andjani Putri (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2025)
The phenomenon of using gamification in the banking sector in Indonesia began with the emergence of digital bankings. As digital bankinging continues to grow rapidly, competition is becoming increasingly tighter. To win this competition, digital bankinging utilizes various promotional strategies, including gamification. The purpose of this research is to test the influence of gamification elements on engagement. This study was conducted quantitatively with 155 respondents from digital bankinging (DB) users. Primary data was collected via questionnaires using Google Forms, a survey which was later analyzed descriptively. Data processing SEM-PLS reveals that element gamification is suggestn to be valuable and practical for engagement. The investigation has shown that all gamification elements had positive effects on engagement. Tests conducted on male and female consumers found that all gamification elements influenced engagement, with male customers.. Meanwhile, for female consumers, points, badge and challenges influence engagement, while levels do not.